EFFICIENCY OF FLOODING BY DEVELOPING RELIABLE SUBNETWORK METHODS ON FIBBING ARCHITECTURE IN THE HYBRID ENVIRONMENT SDN - Dino Budi Prakoso; Royyana Muslim Ijtihadie; Tohari Ahmad (JUTI: Jurnal Ilmiah Teknologi Informasi, 2021)
In the technology world especially in the field of current network of Autonomous Systems connectivity (AS) is indispensable. Especially against the dynamic routing protocols that are often used compared to static routing protocols. In supporting this current network, it takes efficient and effective routing protocols capable of covering a sizable scale. Software Defined Network (SDN) is a technological innovation in the network world that has a separate Control Plane and Data Plane that makes it easy to configure on the Control Plane side. Control Plane is the focal point on a process of bottleneck in SDN architecture. Performance is a critical issue in large-scale network implementations because of the large demand load occurring in the Control Plane by generating low throughput value. This research will be conducted testing on the Hybrid network of SDN by using OSPF routing protocol, based on the Fibbing architecture implemented on the system network Hybrid SDN also able to assist in improving performance, but there are constraints when sending flooding which is used as a fake node forming. Many nodes are not skipped as distribution lines in the formation of a fake node, in which case it will certainly affect the value of throughput to be unstable and decrease. This can be overcome by using the Isolation Domain method to manage the LSA Type-5 flooding efficiency.